Adjustable ultrafast response in hyperbolic metamaterials through double resonances. (18th October 2021) - Xin, Jian; Song, Yinglin; Gao, Junhua; Wang, Yuxiao; Zhang, Xueru
Abstract: Active control of the ultrafast nonlinear optical response in plasmonic nanostructures is essential for the applications of nano-photonics. However, the optical response of noble metal is hindered by the electron dynamics. Here, we demonstrate that the nonlinear absorption properties of silver nanorod arrays could be modulated in the sub-picosecond range by adjusting the incident angle of light. The pump-probe experiment confirmed the response time can be modulated from 2.439 ps to 413 fs by changing the incident angle. Further simulation indicated that the origin of the modulation is the combined effect of the surface plasmon resonance and epsilon-near-zero resonance supported by the samples. Electron temperature shows different effects on the two resonances, leading to the change in the recovery rate of the transmittance during the decrease of the electron temperature. The contributions of the two resonances to nonlinear absorption were presented respectively. The conditions for controlling the relaxation time via multiple resonances were also proposed.